Climate Change Effects on Cucumber Viruses and Their Management - Zhimin Yin; Bartłomiej Zieniuk; Magdalena Pawełkowicz (Agriculture)
The agricultural sector is facing unprecedented challenges as a result of climate change. As temperatures continue to rise and weather patterns shift, the dynamics of plant–virus interactions are significantly altered, requiring innovative solutions to ensure global food security. This review article examines the relationship between climate change and the prevalence and severity of cucumber viral diseases, their impact on cucumber yield and quality, and the subsequent economic implications, focusing on critical pathogens such as cucumber mosaic virus (CMV), cucumber leaf spot virus (CLSV), or cucumber vein yellowing virus (CVYV). It also aims to provide a comprehensive overview of the current state of knowledge and identify critical areas for future research and development in response to climate change. The review examines potential solutions to address these challenges. These include exploring the development of virus-resistant cucumber varieties and the use of RNA-based technologies for virus control.